Spatiotemporal Evolution Analysis of Population Distribution in the Metropolitan Areas of the Three Central Cities in the Yellow River Basin - Sun, Meiqi (International Journal of Natural Resources and Environmental Studies, 2025)
Based on the worldpop population density data, this paper compares and studies the spatial distribution and change characteristics of population in the Yellow River Basin metropolitan area since 2000, and takes the three central urban metropolitan areas of Zhengzhou, Xi’an and Jinan as examples to analyze the characteristics of population distribution change within the metropolitan area. The results show that from 2000 to 2020, there was no significant change in the population distribution pattern of the metropolitan area in the basin, and the distribution of population density showed the pattern characteristics of "high in the southeast and low in the northwest", mainly concentrated in the middle and lower reaches of the basin, and showed a decreasing trend from the downstream to the middle to the upstream. (2) The steady population growth and rapid growth areas are mainly concentrated in the metropolitan areas of Xi’an, Zhengzhou and Jinan, while the population density of the metropolitan areas of Xining, Yinchuan, Hohhot and Lanzhou in the upstream areas is significantly low, and the surrounding areas of the central city show the phenomenon of population growth stagnation and a large number of agglomeration of shrinkage areas. (3) From 2000 to 2020, the maximum population density in the metropolitan area of the three central cities continued to increase, and the trend of expansion from the central city to the surrounding cities showed in the metropolitan area, indicating that the population distribution was gradually moving towards equilibrium.